Ultrasmall PEI-Decorated Bi2Se3 Nanodots as a Multifunctional Theranostic Nanoplatform for in vivo CT Imaging-Guided Cancer Photothermal Therapy - Peng Zhang (Frontiers Media S.A., 2021)
Bi-based nanomaterials, such as Bi2Se3, play an important part in biomedicine, such as photothermal therapy (PTT) and computed tomography (CT) imaging. Polyethylenimine (PEI)-modified ultrasmall Bi2Se3 nanodots were prepared using an ultrafast synthetic method at room temperature (25°C). Bi2Se3 nanodots exhibited superior CT imaging performance, and could be used as effective photothermal reagents owing to their broad absorption in the ultraviolet–visible–near infrared region. Under irradiation at 808 nm, PEI-Bi2Se3 nanodots exhibited excellent photothermal-conversion efficiency of up to 41.3%. Good biocompatibility and significant tumor-ablation capabilities were demonstrated in vitro and in vivo. These results revealed that PEI-Bi2Se3 nanodots are safe and a good nanotheranostic platform for CT imaging-guided PTT of cancer.